THE METHODS OF TEACHING SPEAKING TO B1 LEVEL LEARNERS - Ro‘ziboyeva Binafsha,; Ravshanova Zebiniso,; Razzoqova Risolat, (Ustozlar uchun, 2025)
Teaching speaking to B1 level learners is a crucial step in their language development. At this stage, learners move from basic sentence-level speech to more extended and interactive communication. This article examines various effective methods, principles, and classroom strategies that help students improve fluency, accuracy, and confidence in speaking.